ANALISIS PRESEPSI KESALAHAN SISWA SMP PADA SOAL MATERI STATISTIKA DITINJAU DARI PERBEDAAN GENDER - Marwah Amelia; Ratna Sariningsih; Wahyu Hidayat (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2020)
The purpose of this study was to analyze students' perceptions of errors in statistical material in terms of gender differences. This research was conducted in class IX SMP Negeri 1 Tirtajaya, Karawang regency by taking a sample of 8 people, male and female students according to their knowledge. The research is a study conducted using descriptive qualitative methods with the material used is statistical material. The process of data analysis is done in stages, namely collecting data, presenting data, and drawing conclusions. Data collection was obtained from data collection in the form of data solving statistical test questions by analyzing student errors in solving statistical problems. Presentation of data is presented in brief descriptions, pictures, and presentation of descriptions in the form of descriptive analysis of errors in solving basic statistical problems according to Newman. Conclusions are drawn from the review of the data that has been presented and examine the explanation and causal relations in the analysis process. The results showed that female students were superior in solving problems in statistical material compared to male students. There were still errors in solving these problems.